Like a Bridge over Troubled Waters: the Death of the Mother a Comparative Study in Literature Between USA and French Feminist Poetry - Karasavvidou, Eleni (European Journal of Multidisciplinary Studies, 2017)
The power of fear and the need for happiness are equal, wrote Adorno in Minima Moralia (2001, p. 223) describing in a phrase the inevitable contradictions of the human condition. Mother and motherhood reflect both, fear and need, transforming eachother in a constant dialogue that mediates the various expressions of our sociopsychological transformations. A dialogue unready to be completed as long as our worldviews sustain hierarchies that manipulate the need and the fear.